A phase 1/2 dose‐finding, safety, and activity study of cabazitaxel in pediatric patients with refractory solid tumors including tumors of the central nervous system. Issue 9 (11th May 2018) - Manley, Peter E.; Trippett, Tanya; Smith, Amy A.; Macy, Margaret E.; Leary, Sarah E.S.; Boklan, Jessica; Cohen, Kenneth J.; Goldman, Stewart; Kilburn, Lindsay B.; Dhall, Girish; Devin, Jeanne; Herzog, Cynthia E.; et al.
Abstract: Background: This phase 1/2 study (NCT01751308) evaluated cabazitaxel in pediatric patients. Phase 1 determined the maximum tolerated dose (MTD) in patients with recurrent/refractory solid tumors, including central nervous system (CNS) tumors. Phase 2 evaluated activity in pediatric recurrent high‐grade glioma (HGG) or diffuse intrinsic pontine glioma (DIPG). Procedure: In phase 1, a 3 + 3 dose‐escalation study design was followed. Cabazitaxel was administered at a starting dose of 20 mg/m 2 . Dose‐limiting toxicities (DLTs) during cycle 1 were assessed to determine the MTD. Tumor response and cabazitaxel pharmacokinetics were also assessed. In phase 2, patients received cabazitaxel at the MTD determined in phase 1. Tumor responses were assessed every 9 weeks (modified Response Assessment in Neuro‐oncology criteria). Progression‐free survival and cabazitaxel pharmacokinetics were evaluated, and overall survival was estimated. Results: In phase 1, 23 patients were treated, including 19 with CNS tumors. One patient had a partial response; five had stable disease for >3 cycles. Common adverse events included fatigue, diarrhea, nausea and vomiting, febrile neutropenia, and hypersensitivity reactions. Two of three DLTs (febrile neutropenia) occurred with a dose of 35 mg/m 2 ; the MTD was 30 mg/m 2 . Slightly higher cabazitaxel clearance was observed compared with adult trials. In phase 2, 16 patients (eight HGG and eight DIPG) were enrolled; 11 were evaluable for response and five withdrew (three due to anaphylaxis). All 11 patients progressed within four cycles. No responses were observed; the study was stopped due to futility. Conclusions: The safety profile of cabazitaxel was consistent with previous studies. The MTD (30 mg/m 2 ) was higher than the adult MTD. Cabazitaxel did not demonstrate activity in recurrent/refractory HGG or DIPG.